Partnerships With Providers: Reflections From Parents of Children With Type 1 Diabetes. (October 2014) - Ayala, Judith; Howe, Carol; Dumser, Susan; Buzby, Marianne; Murphy, Kathryn
Sixty-three parents with a child or an adolescent with type 1 diabetes participated in this study that focused on what helped them "live well with diabetes." Beyond medical expertise, parents described a partnering relationship with their provider as one of the factors that supported their efforts to live well with diabetes. Parents reported that a partnership was enhanced when the provider had the ability to understand the dynamic nature of the journey in living with diabetes, connect with their family and set the tone by inviting them to openly communicate about all aspects of family life impacting diabetes care, recognize when and how the provider may have to assume the role of Captain of the Ship in times of need, and empathize and respond therapeutically to intense emotions inherent in managing diabetes over time.